Penerapan Model Pembelajaran Make a Match dalam Meningkatkan Hasil Belajar Aqidah Akhlak Siswa Madrasah Tsanawiyah Negeri 5 Kota Jambi - Safitri, Fadilah; Surayya, Ely; Wiratama, Arif; Habibi, M. Fadli (Sekolah Tinggi Ilmu Syariah Ummul Ayman Pidie Jaya, 2023)
Class VIII-C student learning outcomes experience classical mastery. This is motivated by how active students are and how extensive understanding of the material impacts learning outcomes. For this reason, the purpose of this study was to find out whether the application of the Make a Match model to learning aqeedah morals can improve student learning outcomes in class VIII-C Madrasah Tsanawiyah Negeri 5 Jambi City. This type of research is classroom action research. The class that was used as the class under study was class VIII-C as a whole the students in that class. Data collection techniques using multiple choice questions, interviews, observation and documentation. Based on the results of applying the Make a Match learning model, it is categorized as very good. This can be seen from the scores of student learning outcomes after the learning process in each cycle has increased. Based on the learning outcomes scores obtained by students from cycle I, the average value was 73,3 or 17 students had completed learning, cycle II had an average score of 86,3 or 27 students had completed learning. So it can be concluded that the average increase in learning outcomes after the application of the Make a Match learning model that occurs from cycle I to cycle III is 79.8, which means that through the application of the Make a Match learning model it is able to improve learning outcomes to improve student learning outcomes.